Information and Communication Systems' Impact on Healthcare Quality: Insights from Medical City Complex Employees - Ola.B. Hashim (Academia Open, 2024)
This descriptive analytical study investigates the pivotal role of information and communication systems in enhancing the quality of medical services, drawing upon the perspectives of employees at Medical City Complex. Employing a semi-experimental approach with 40 participants from the Department of Medicine, the research delves into the understanding of information and communication systems and quality medical care. The study employs a three-section questionnaire, encompassing demographic information, dimensions of healthcare quality, and dimensions of information and communication systems. Validity and reliability of the questionnaire were rigorously established. The findings unveil significant trends, particularly in factors such as age and years of service, illustrating their links to healthcare quality and information and communication systems. Detailed analyses of healthcare quality dimensions (Tangibles, Reliability, and Assurance) and information system aspects (Management, Organization, and Information Technology) are presented. The study concludes by elucidating the impact of independent variables on dependent variables, providing invaluable insights for future research and decision-making in the healthcare sector, ultimately enhancing the quality of medical care and information systems. Highlights: Investigates the impact of information and communication systems on medical service quality. Utilizes a semi-experimental approach with 40 Department of Medicine employees. Highlights the influence of age and years of service on healthcare quality and information systems. Keywords: Healthcare Quality, Information and Communication Systems, Employee Perspectives, Validity and Reliability, Healthcare Improvement